Pengaruh Sistem Informasi Akuntansi Via Aplikasi Mobile Berbasis Fintech dan Pengaruh Literasi Keuangan Terhadap Kinerja Keuangan UMKM Di Kecamatan Karawang Barat - Azizi, Abi Rafdi Al; Yanti, Yanti; Lasmini, Lilis (Peneliti.net, 2024)
This research aims to determine the influence of accounting information systems via fintech-based mobile applications on the financial performance of MSMEs in West Karawang District and the influence of financial literacy on the financial performance of MSMEs in West Karawang District. This research method uses quantitative methods with data taken using primary data. The sampling technique was determined using the purposive sampling method. The samples taken in this research were 100 samples with the criteria of MSME business owners in West Karawang District who had been in business for at least one year. Data collection was carried out by distributing questionnaires via Google Forms. The data analysis technique used to process data in this research uses PLS with Smart PLS 4.0 software.